Interaction between ABA and NO in plants under abiotic stresses and its regulatory mechanisms - Xu, Junrong; Lu, Xuefang; Liu, Yunzhi; Lan, Weisen; Wei, Zhien; Yu, Wenjin; Li, Changxia (Frontiers in Plant Science, 2024)
Abscisic acid (ABA) and nitric oxide (NO), as unique signaling molecules, are involved in plant growth, developmental processes, and abiotic stresses. However, the interaction between ABA and NO under abiotic stress has little been worked out at present. Therefore, this paper reviews the mechanisms of crosstalk between ABA and NO in the regulation of plants in response to environmental stresses. Firstly, ABA-NO interaction can alleviate the changes of plant morphological indexes damaged by abiotic stresses, for instance, root length, leaf area, and fresh weight. Secondly, regulatory mechanisms of interaction between ABA and NO are also summarized, such as reactive oxygen species (ROS), antioxidant enzymes, proline, flavonoids, polyamines (PAs), ascorbate-glutathione cycle, water balance, photosynthetic, stomatal movement, and post‑translational modifications. Meanwhile, the relationships between ABA and NO are established. ABA regulates NO through ROS at the physiological level during the regulatory processes. At the molecular level, NO counteracts ABA through mediating post-translational modifications. Moreover, we also discuss key genes related to the antioxidant enzymes, PAs biosynthesis, ABA receptor, NO biosynthesis, and flavonoid biosynthesis that are regulated by the interaction between ABA and NO under environmental stresses. This review will provide new guiding directions for the mechanism of the crosstalk between ABA and NO to alleviate abiotic stresses.